Radio Dakwah dan Upaya Menangkal Kristenisasi - Suharjo, Suharjo; Fatoni, Uwes (Asosiasi Prodi Komunikasi dan Penyiaran Islam (Askopis), 2017)
Some Islamic preachers use the mass media in da'wah including they are in Cigugur Kuningan using radio in conveying messages of da'wah to mad'u especially they are vulnerable to object of Christianization. This paper reveals the efforts of Radioqu 104.8 FM in counteracting the Christianization mission in Cigugur Kuningan. Based on research radioqu 104.8 FM has da'wah role in counteracting Christianization in Cigugur, Kuningan through delivering of da'wah information namely: broadcasting of Islamic science, broadcasting Islam news, broadcasting information of society need, and broadcasting time of prayer. Radioqu 104.8 FM also educate the community to counteract the Christianization by applying the educational function through the discussion of people's problems, educating through exemplary stories, and educating healthy lifestyles. Moreover, Radioqu 104.8 FM gives influence in society to counteract Christianity through efforts to encourage diligent worship, influence to defend aqidah, influence the mindset of non-Muslims that Islam is a religion of peace, and develop Islamic art. Dakwah efforts through the utilization of mass media complement the activities of conventional da'wah through Islamic preaching.Banyak da’i memanfaatkan media massa dalam berdakwah seperti para da’i di kecamatan Cigugur Kuningan yang memanfaatkan radio dalam menyampaikan pesan-pesan dakwah kepada mad’u khususnya yang rentan kristenisasi. Tulisan ini mengungkapkan upaya Radioqu 104.8 FM dalam menangkal misi kristenisasi di Kecamatan Cigugur Kuningan. Berdasarkan hasil penelitian peranan dakwah Radioqu 104.8 FM dalam menangkal kristenisasi di Cigugur, Kuningan dilakukan melalui penyampaian informasi dakwah yaitu: menyiarkan ilmu keislaman, menyiarkan berita Islam, menyiarkan informasi kebutuhan masyarakat, dan menyiarkan waktu shalat. Radioqu 104.8 FM juga turut mendidik masyarakat untuk menangkal kristenisasi dengan menerapkan fungsi mendidik melalui tanya jawab masalah umat, mendidik melalui kisah teladan, dan mendidik pola hidup sehat. Demikian juga Radioqu 104.8 FM berupaya mempengaruhi masyarakat untuk menangkal kristenisasi melalui upaya mendorong rajin ibadah, mempengaruhi untuk mempertahankan akidah, mempengaruhi pola pikir umat non Muslim bahwa Islam agama damai, dan mengembangkan seni Islam. Upaya dakwah melalui pemanfaatan media ini melengkapi kegiatan dakwah konvensional yang sudah berjalan melalui ceramah.